Sistem Upah Toserta dan Grosir Riska dalam Perspektif Manajemen Pengupahan Islam - Rindi Cantika Dewi; Ashfa Fikriyah (Journal of Islamic Economics (JoIE), 2024)
Introduction: Riska Department Store and Wholesaler has a wage system that provides wages once a month and sets wages for new employees at IDR 600,000. If the employee demonstrates good performance and is absent no more than twice, the owner usually increases the wage from month to month. Research Methods: This research is a type of qualitative research with a descriptive approach, using field methods with data collection techniques such as observation, interviews, and documentation. Results: The research results show that Riska Department Store has used the POAC management function and implemented two principles to determine the amount of employee wages: the principle of justice and the principle of appropriateness. In Islamic wage management, the techniques used are quite good, as evidenced by the business owner providing wages to employees every time they work at Riska Department Stores and Wholesalers. In Islam, there are also two principles: justice and the principle of decent and reasonable compensation. Conclusion: In summary, Riska Department Store and Wholesaler not only emphasizes fairness and appropriateness in its wage management but also integrates Islamic principles of just compensation. This approach highlights a commitment to equitable remuneration practices, crucial for maintaining employee satisfaction and compliance with Islamic ethical standards in business operations.